Nutrient value and in vitro rumen fermentation characteristics of pumpkin vines, sweet potato vines, grape vines and pepper straw for yaks - He, Liang; Yang, Zhirui; Zhu, Yunyun; Pan, Yao; Li, Rui (Frontiers in Animal Science, 2026)
IntroductionReducing feed costs and promoting sustainability are key challenges in yak production. This study aimed to comprehensively evaluate the potential of four locally available agricultural by-products—pumpkin vines (PV), sweet potato vines (SPV), grape vines (GV), and pepper straw (PS)—as alternative feed resources for yaks. MethodsFirst, the chemical composition (dry matter-DM, crude protein, neutral detergent fiber-NDF, acid detergent fiber-ADF) of each by-product was analyzed. Subsequently, a 72-hour in vitro ruminal fermentation experiment was conducted to evaluate fermentation parameters. Finally, high-throughput sequencing was used to analyze associated shifts in the rumen bacterial microbiota, and Spearman correlation analysis was performed to link key microbial genera with fermentation outcomes.Results and Discussion1) GV and PV had a higher crude protein content, while PS had the highest levels of dry matter (DM), neutral detergent fiber (NDF) and acid detergent fiber (ADF, P< 0.001); 2) After 72 hours of in vitro fermentation, PV and SPV had superior gas production and nutrient degradability (DM, NDF and ADF, P< 0.001); 3) The fermentation parameters showed that SPV and GV promoted more efficient fermentation, characterized by a lower pH and a lower acetate-to-propionate ratio, but higher microbial protein (MCP) levels (P< 0.001). PV yielded the highest concentrations of volatile fatty acids (P< 0.001). 4) Rumen microbiota analysis identified distinct, diet-specific enrichments of bacterial genera (P< 0.05), including: g_Fusobacterium and g_Basfia in PV; g_Rikenellaceae_RC9_gut_group and g_Streptococcus in SPV; g_norank_f:p-251-o5 and g_Butyricicoccus in PS; g_Lachnospira and g_Pseudobutyrivibrio in GV Critically, Spearman correlation analysis linked these microbial shifts to fermentation outcomes: Genera such as g_Fusobacterium and g_Basfia were found to be positively correlated with MCP (P< 0.05), while g_Rikenellaceae_RC9_gut_group and g_Butyricicoccus were positively associated with total volatile fatty acids (P< 0.05). In conclusion, while all four by-products show potential as alternative feeds, SPV and GV show better overall feeding value for yaks, supported by their balanced nutrient composition, improved fermentability, and positive associations with rumen microbiota. This integrated assessment provides a strong basis for utilizing them to enhance the sustainability of yak production.